Changes in Leaf Anatomical Traits Enhanced Photosynthetic Activity of Soybean Grown in Hydroponics with Plant Growth-Promoting Microorganisms - Paradiso, Roberta; Arena, Carmen; De Micco, Veronica; Giordano, Maria; Aronne, Giovanna; De Pascale, Stefania (Frontiers in Plant Science, 2017)
The use of hydroponic systems for cultivation in controlled climatic conditions and the selection of suitable genotypes for the specific environment help improving crop growth and yield. We hypothesized that plant performance in hydroponics could be further maximised by exploiting the action of plant growth-promoting organisms (PGPMs). However, the effects of PGPMs on plant physiology have been scarcely investigated in hydroponics. Within a series of experiments aimed to identify the best protocol for hydroponic cultivation of soybean [Glycine max (L.) Merr.], we evaluated the effects of a PGPMs mix, containing bacteria, yeasts, mycorrhiza and trichoderma beneficial species on leaf anatomy, photosynthetic activity and plant growth of soybean cv. ‘Pr91m10’in closed nutrient film technique (NFT). Plants were grown in a growth chamber under semi-aseptic conditions and inoculated at seed, seedling and plant stages, and compared to non-inoculated (control) plants. Light and epi-fluorescence microscopy analyses showed that leaves of inoculated plants had higher density of smaller stomata (297 vs 247 n/mm2), thicker palisade parenchyma (95.0 vs 85.8 μm), and larger intercellular spaces in the mesophyll (57.5% vs 52.2%), compared to non-inoculated plants. The modifications in leaf functional anatomical traits affected gas exchanges; in fact starting from the reproductive phase, the rate of leaf net photosynthesis was higher in inoculated compared to control plants (8.69 vs 6.13 μmol CO2 m-2 s-1 at the beginning of flowering). These data are consistent with the better maximal PSII photochemical efficiency observed in inoculated plants(0.807 vs 0.784 in control); conversely no difference in leaf chlorophyll content was found. The PGPM-induced changes in leaf structure and photosynthesis lead to an improvement of plant growth (+29.9% in plant leaf area) and seed yield (+36.9%) compared to control. Our results confirm that PGPMs may confer benefits in photosynthetic traits of soybean plants even in hydroponics (i.e. NFT), with positive effects on growth and seed production, prefiguring potential application of beneficial microorganisms in plant cultivation in hydroponics.